2012
DOI: 10.1016/j.archger.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, components, and correlates of metabolic syndrome (MetS) among elderly Muscovites

Abstract: The goal of this study is to estimate the prevalence of Metabolic Syndrome (MetS), together with its components and correlates, among elderly Russians. Our population-based sample included randomly selected residents of Moscow aged 55 and older: 955 women with an average age of 67.6, and 833 men with an average age of 68.9. MetS was defined according to NCEP-ATPIII. The prevalence of MetS was found to be 41.7% in women and 26.8% in men. It tended to decrease with age in men, but not in women. MetS was inversel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 52 publications
3
20
0
5
Order By: Relevance
“…MetS was found to be associated with markers of insulin resistance (IR), low-grade inflammation, and insufficient fibrinolysis. 22 We also find higher prevalence of MetS in our study and it was 55.9% among women and 40.2% among men (P < 0.05). The highest prevalence was present in patients aged more than 50 years (87%, P <0.05).…”
Section: Metabolicsupporting
confidence: 63%
“…MetS was found to be associated with markers of insulin resistance (IR), low-grade inflammation, and insufficient fibrinolysis. 22 We also find higher prevalence of MetS in our study and it was 55.9% among women and 40.2% among men (P < 0.05). The highest prevalence was present in patients aged more than 50 years (87%, P <0.05).…”
Section: Metabolicsupporting
confidence: 63%
“…For example, the recent study on the methabolic syndrome demonstrated that while Muscovite women experience much higher prevalence of obesity, men experience much higher incidence of myocardial infarction, higher prevalence of hypertension, and hyperglycemia [51]. It was also reported that Russian men have substantially better general and phychological health than Russian women, they have much higher levels of smoking and alcohol drinking and higher incidence of related cancers [5255].…”
Section: Discussionmentioning
confidence: 99%
“…Problematic drinking, smoking, and obesity are inversely associated with education in SAHR (results not shown; see also Metelskaya et al, 2012), and these health behaviors have been shown to be associated with inflammation (Ferrante, 2007; Gonçalves et al, 2011; Szabo and Mandrekar, 2009). Obesity and inflammation are consistently linked to the extent that many consider obesity a state of chronic inflammation (de Heredia et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…Second, education is preferable to income and occupation as an indicator of SES in Russia specifically; this preference is reflected in most epidemiological and public health studies linking mortality and health with socioeconomic status in Russia (Dennis et al, 1993; Glei et al, 2013a; Metelskaya et al, 2012; Shkolnikov et al, 2004b, 1998). Income measurement in Russia has been more challenging than in other developed countries.…”
Section: Methodsmentioning
confidence: 99%